Pruning Management in Albizia Species: Effect on Tree Growth, Understorey Forage Production and Floral Composition - Pai, P; Yadav, R S; Shaner, Arun K; Ram, Munna; Singh, U P (Annals of Arid Zone, 2016)
An experiment was taken up at National Research Centre for Agroforestry, Jhansi, to determine suitable species of Albizia and an optimum pruning practice for increased natural forage production under tree canopy. Three species for Albizia (A. amara, A. lebbek and A. procera) were evaluated under four pruning heights (0, 25, 50 and 75% from the ground level) in split plot design with three replications. There were no significant differences in survival percentages, growth of Albizia spp. and forage production before pruning, but growth and forage production increased after pruning with maximum under 75% pruning. A. procera was superior in' terms of growth, early development of canopy, dry leaf fodder and fuel wood production. Pruning of Albizia spp. at 50 or 75% intensity resulted into dominance and composition of Dichanthium annulatum, legumes and decrease in forbs indicating a good sign in improvement in quality of natural grassland. Introduction of Albizia spp. in natural grassland also brought improvement in soil fertility. Key words: Pruning, Albizia spp., soil enrichment, composition, dominance, natural grassland.